The Impact of Flexible Working Hours, Remote Working, and Work Life Balance to Employee Satisfaction in Banking Industry during Covid-19 Pandemic Period - Kresna Chandra Putra; Tedo Aris Pratama; Rionaldo Aureri Linggautama; Sekar Wulan Prasetyaningtyas (Journal of Business and Management Review, 2020)
During the situation like Coronavirus COVID -19 pandemic that happened in 2020, forcing various banking companies to make adjustments and changes to their work system. The flexible working system is one of the most widely used, which has an impact on workers especially during this pandemic conditions. The impact of the change in work system in banking sector is interesting to study, especially since the banking industry in Indonesia still mostly uses conventional work systems. . This study aims to measure the impact of flexible working hours (FWH), remote working (RW), and work life balance (WLB) on employee job satisfaction in the banking industry during the pandemic. In this study, data were collected using quantitative, non-probability, purposive sampling methods via online questionnaires, which were distributed to employees in the banking sector during the pandemic period in Jabodetabek area. With total of 160 respondents who were used to perform analysis using the PLS-SEM method which was carried out with the SMART-PLS software. This study found that in pandemic conditions, achieving WLB conditions will have a positive impact on job satisfaction. The implementation of the RW system itself has a positive impact in helping to achieve the WLB conditions that are felt by banking workers in the Jabodetabek area, in contrast to the FWH system which does not have a similar effect on WLB. In addition, this study also provides an academic basis for the use of flexible working hour and remote working systems to increase job satisfaction, especially in the banking industry.